Bruxism - a common problem in the adult population - Szymon Markowiak; Marta Wardęszkiewicz; Wiktoria Jabłońska; Amelia Kasprzak; Maciej Świercz; Monika Truchta; Aleksandra Mańkowska; Agata Kolano; Anna Pejas (Kazimierz Wielki University, 2024)
Introduction and Purpose: Bruxism, the involuntary grinding or clenching of teeth, is a common problem in the adult population. This research aims to provide an overview of bruxism, focusing on its etiology, symptoms, diagnosis, and treatment, with the ultimate goal of enhancing understanding and promoting effective management strategies.   Description of the State of Knowledge: Bruxism has been recognized as a prevalent dental disorder affecting a significant portion of the adult population. The condition involves the repetitive motion of grinding or clenching teeth, often occurring during sleep or subconsciously during waking hours. While its exact etiology remains multifactorial, stress, anxiety, malocclusion, and lifestyle factors are frequently implicated. The symptoms range from dental damage and jaw pain to headaches and disturbed sleep patterns, necessitating a comprehensive understanding of the disorder for accurate diagnosis and appropriate intervention. Current knowledge highlights the importance of early detection and tailored therapeutic approaches to alleviate symptoms and prevent complications.   Summary: This article synthesizes existing knowledge on bruxism, addressing its etiological factors, clinical manifestations, diagnostic modalities, and available treatment options. By consolidating the state of knowledge, this research contributes to a more comprehensive understanding of bruxism and facilitates the development of evidence-based approaches for its management.